Implicaciones de la criminalización del aborto en Ecuador (Tema Central) - Guerra Rodríguez, Elsa Genoveva (2018)
The article demonstrates the ineffective and anachronistic nature of the criminalization of abortion, since in addition to generating serious violations of women’s rights, it has caused that the female morbidity and mortality rates continue growing, and that the family nucleus, society and the State are the affected. Additionally, it makes visible the way in which the criminalization of the interruption of pregnancy is configured as a device for the control of the female body and the requirement of the observance of a reproductive contract imposed by the patriarchal system. Finally, it raises some alternatives to the need to reduce the alarming rates of clandestine abortion in Ecuador, and the feminist demand for recognition of women as full subjects capable of self-determination in the reproductive field.